Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/toxics11020176
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Zooplankton-Toxic Cyanobacteria Interactions: A Review

Abstract: Cyanobacterial blooms have been recognized as a problem in fresh water for about 150 years. Over the past 50 years, experimental studies on the subject have gained importance considering the increasing need to control toxic cyanobacterial blooms. This article presents information on the different lines of research that have been undertaken on zooplankton–cyanobacteria interactions over the past 50 years. These include information on filtering/ingestion rates and phytoplankton preferences of small and large rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Zhang et al [78] reported that these species exhibit the elongation of their spines in response to elevated predation by cyclops copepods and modulate the length of their spines to a shorter state when confronted with heightened predation from fish. Additionally, previous studies also documented that Brachionus exhibit notable resilience to cyanobacterial toxins and this resilience enables them to effectively exploit colonial blue-green algae and endure their blooms [79]. The capacity of Brachionus and Keratella to endure these adverse influences elucidates their positioning as two of the genera capable of thriving in eutrophic environments.…”
Section: Discussionmentioning
confidence: 89%
“…Zhang et al [78] reported that these species exhibit the elongation of their spines in response to elevated predation by cyclops copepods and modulate the length of their spines to a shorter state when confronted with heightened predation from fish. Additionally, previous studies also documented that Brachionus exhibit notable resilience to cyanobacterial toxins and this resilience enables them to effectively exploit colonial blue-green algae and endure their blooms [79]. The capacity of Brachionus and Keratella to endure these adverse influences elucidates their positioning as two of the genera capable of thriving in eutrophic environments.…”
Section: Discussionmentioning
confidence: 89%
“…49 Variation may occur due to stochastic changes in hydrodynamics. 50 Daphnia, despite their ability to create periods of clear water, are mostly unable to feed on bloom-forming colonial or filamentous cyanobacteria, 51 as the size of the particles the daphnids filter is limited. [52][53][54] The lifespan of Daphnia is very short, and its seasonal succession is rapid.…”
Section: From Hope To Hopelessnessmentioning
confidence: 99%